Th9 and Th17 Cells in Human Ulcerative Colitis-Associated Dysplastic Lesions - Guanglin Cui; Aping Yuan; Sveinung W Sørbye; Jon Florholmen (Clinical Medicine Insights: Oncology)
Background: Inflammation is the most important deriving force for the development of colitis-associated colorectal cancer (CAC) through the Inflammation-Pretumor dysplasia-CAC sequence. T helper (Th) subsets Th9 and Th17 cells can potentially stimulate inflammation in the ulcerative colitis (UC). Therefore, Th9 and Th17 cells may play a promoting role in the colitis-associated dysplasia (CAD). Methods: Using immunohistochemistry (IHC), we evaluated the presentation patterns and densities of T lymphocytes, Th9 and Th17 cells in human UC and CAD tissues. Results: A general increasing trend of CD3-positive T lymphocytes, P.U.1-positive Th9 and interleukin (IL)-17A-positive Th17 cells was illustrated throughout the normal-UC-CAD sequence, IHC images showed that these cells were very prominent in the lamina propria, and some cells were also observed in the epithelium in the CAD tissues. Density analysis revealed that numbers of Th9 and Th17 cells were progressively increased in the CAD tissues as compared with the UC and control tissues. In general, densities of Th9 and Th17 cells in the lamina propria were slightly higher in the non-adenoma-like dysplasia (NALD) tissues than that in the adenoma-like dysplasia (ALD) tissues. However, densities of neither Th9 nor Th17 cells in both the ALD and NALD subgroups were associated with the degree of dysplasia in CAD lesions. Conclusion: Accumulated Th9 and Th17 cells contribute to the immune cellular composition in the CAD tissues and may represent the early conditional change for the Dysplasia-CAC transition.